2020
DOI: 10.1136/bmjopen-2019-035552
|View full text |Cite
|
Sign up to set email alerts
|

Protocol for the economic evaluation of metacognitive therapy for cardiac rehabilitation participants with symptoms of anxiety and/or depression

Abstract: IntroductionCardiac rehabilitation (CR) is offered to reduce the risk of further cardiac events and to improve patients’ health and quality of life following a cardiac event. Psychological care is a common component of CR as symptoms of depression and/or anxiety are more prevalent in this population, however evidence for the cost-effectiveness of current interventions is limited. Metacognitive therapy (MCT), is a recent treatment development that is effective in treating anxiety and depression in mental health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…No adverse treatment-related effects were reported. An economic evaluation is planned and will be published separately (21).…”
Section: Full-scale Trial Of Effectiveness Of Group-mct In Cr (Nct024...mentioning
confidence: 99%
“…No adverse treatment-related effects were reported. An economic evaluation is planned and will be published separately (21).…”
Section: Full-scale Trial Of Effectiveness Of Group-mct In Cr (Nct024...mentioning
confidence: 99%
“…19 The PATHWAY Programme funded under the UK NIHR Programme Grants for Applied Research (RP-PG-1211-20011), aims to improve access to more effective psychological interventions for patients attending CR who present with symptoms of depression and/or anxiety. [20][21][22][23] A multicentre, two-arm, single-blind, randomised controlled trial was conducted to compare the clinicaleffectiveness and cost-effectiveness of group-based metacognitive therapy (MCT) plus CR to CR alone. 21 This found that group MCT+CR significantly improved depression and anxiety compared with CR alone.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%